The impact of family structure on schooling outcomes for children in South Africa. - Ndagurwa, Pedzisai. (2014)
This study investigates the impact of family structure on schooling outcomes for children aged 7 to 17 years in South Africa. There is limited recent national research focusing on examining factors affecting schooling outcomes for children beyond economic factors in South Africa. Most literature available is either based on selected provinces, communities and Demographic Surveillance Areas or studied schooling outcomes without delineating the effect of the family structures children live in. This study uses data on a sample of 225 538 children obtained from the Community Survey of 2007 (CS2007) which was conducted by Statistics South Africa. It identifies a taxonomy of family structures unique to South Africa in comparison to other parts of the world especially the developed world given the effects of long term migration and macro-social transformations such as HIV/AIDS, increase in urbanisation, decreasing marriage rates and increasing out-of-wedlock births all of which lead to more complex family structures being observed. The study uses quantitative techniques employing logistic and ordinary least squares regression models to analyse the odds of school enrolment for children and average highest grade completed for age. The results of the study show that family structure impacts on schooling outcomes for children significantly. The study thus arrives at the conclusion that, controlling for all other variables like age, sex, population group, province of residence, socioeconomic status and type of school, family structure has a significant impact on the schooling outcomes of children in South Africa. === M.A. University of KwaZulu-Natal, Durban 2013.